Gruta Nova da Columbeira (Bombarral, Portugal): Site stratigraphy, age of the Mousterian sequence, and implications for the timing of Neanderthal extinction in Iberia - Zilhão, João (2014)
Abstract: The Gruta Nova da Columbeira is recurrently mentioned in the literature concerning the Middle-to-Upper Palaeolithic transition in Iberia as documenting the persistence beyond 30 000 calendar years ago of a Neanderthal-associated Mousterian. This claim is based on conventional radiocarbon dates obtained in the 1960’s and the 1970’s. In order to assess its validity, we undertook archival research to obtain unpublished details concerning the actual composition and chemistry of the dated samples, replicated the dating of samples of the same kind (carbonaceous sediments) and collected in the same deposits from the back of the cave whence came the 1970’s results, and obtained an U-series age estimate for a bone tool from the base of the Mousterian sequence excavated at the entrance of the cave in 1962. We then cross-checked all the stratigraphic and dating information thus assembled against the original field documents. Our results show that (a) the cave entrance sequence formed between MIS-5 and early MIS-3, (b) the deposits at the back of the cave probably formed in the Tardiglacial, and (c) the presence in these deposits of significant amounts of inherited charcoal derived from the entrance area explains the “Early Upper Palaeolithic” (EUP) age determinations obtained for the 1970’s samples. The association of such determinations with the Mousterian has been based on an unwarranted assumption of lateral stratigraphic continuity. While the entrance deposits correspond to an in situ Mousterian sequence, those from the back of the cave are primarily made of clay accumulated under temporary waterlogged conditions, with the few artefacts of Middle Palaeolithic affinities recovered therein being in secondary position. The evidence from Gruta Nova can no longer be used to counter the existence of a late Aurignacian in the region. In southern and western Iberia, the Neandertal-to-modern and Middle-to-Upper Palaeolithic transitions occurred no later than about 37 000 years ago.